Peran Home Industry Dalam Meningkatkan Kemandirian Ekonomi Pekerja Perempuan Kabupaten Kediri - Nur Puspita Sari, Fadia Rizky; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2025)
Home industry has an important role in boosting the country’s economy. It helps improve the community’s economy by creating jobs and increasing people’s income. This research aims to analyze the role of the krecek home industry in increasing the economic independence of female workers and to analyze the economic independence of female workers who work in the krecek industry. This research is qualitative research with a descriptive approach which is analyzed using data reduction and based on technical triangulation as a test of data validity. The results of this research show that the krecek home industry has a role in increasing the economic independence of female workers. This can be seen from the increase in income and economy experienced by female workers and they become more responsible and have initiative when solving problems they experience. In terms of economic independence, female workers here cannot yet be called completely financially independent, this is because they are still dependent on consumer debt, do not understand cash flow management, do not have investments because the wages they are given are still not fully sufficient for their needs.